Winner-Take-All Crowdsourcing Contests with Stochastic Production - Cavallo, Ruggiero; Jain, Shaili (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2013)
We study winner-take-all contests for crowdsourcing procurement in a model of costly effort and stochastic production. The principal announces a prize value P, agents simultaneously select a level of costly effort to exert towards production, yielding stochastic quality results, and then the agent who produces the highest quality good is paid P by the principal. We derive conditions on the probabilistic mapping from effort to quality under which this contest paradigm yields efﬁcient equilibrium outcomes, and demonstrate that the conditions are satisﬁed in a range of canonical settings.